Prescribed-time Synchronization of Multiweighted and Directed Complex Networks with Time-Varying Delays via Hybrid Control Method - Yang, Hongmei; Shi, Lin (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we study the problem of the prescribed-time (PT) synchronization for multiweighted directed complex networks (MWDCNs) with time-varying delays via hybrid control method. The nonlinear and coupling terms have N+1 non-identical time-varying delays, which increases the difficulty of our study. The network topology is not assumed to be disconnected, which implies only the outer coupling matrix is required to be asymmetric. The coupling matrix is dealt with the rearrangement of variables (ROT) method. An effective synchronization criterion is established. Finally, the effectiveness of the proposed method is illustrated by a numerical simulation.